TUTURAN DEKLARATIF JENIS, FUNGSI, DAN KESANTUNANNYA DI DALAM WACANA PERCAKAPAN RANAH KELUARGA - Hartati Hartati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2005)
The sources of the article from the result of the research using the speech of the declaration in household discourse. This research attempts to address the following questions: what types of declaratives are used in household discourse, what function they perform, why a certain declarative is used to perform a certain function, and what kinds of politeness observed in the declaratives are used in household discourse. In line with the research problems, the study is aimed at describing types oflndonesian declaratives used in household discourse, describing their functions, explaining why those forms are used to perform the functions, and at discussing their politeness. The underlying theories of this qualitative research are Austin's (1962) speech act theory that deals with the classification of speech acts, modes, pragmatic functions, and Brown and Levinson's politeness principles